Role of multi-walled carbon nanotubes as a growth regulator for Basella alba (Malabar spinach) plant and its soil microbiota - Garima Singh; Sayantan Ghosh; B. Dinakar; Bismita Nayak (Chemical and Biological Technologies in Agriculture, 2022)
Abstract The effect of pure multi-walled carbon nanotubes (MWCNTs) was studied on the development and morphology of the Basella alba plant. The plants were treated with varying sonicated concentrations of MWCNTs. The parameters taken into consideration were germination percentage of seeds, protein content in the plant, estimation of chlorophyll concentration, and the effect on the soil microbial community after treatment with MWCNTs. A boost in vigour index was recorded with the 200 µg ml−1 concentration of MWCNTs. Increment in other parameters like protein content, chlorophyll concentration, and microbial community in soil samples have also been observed. All parameters showed higher efficiency in a concentration-dependent manner of MWCNTs compared to control by testing the significance of results through statistical one-way ANOVA analysis. The uptake of MWCNTs by plants was confirmed by SEM–EDX analysis of treated and control leaf tissue sections. This study concludes that MWCNTs exhibit significant growth effects with no toxicity to Basella alba. Graphical Abstract